Drop-Coating Deposition Raman (DCDR) Spectroscopy as a Tool for Membrane Interaction Studies: Liposome-Porphyrin Complex - Kočišová, Eva; Procházka, Marek; Vaculčiaková, Lenka (Applied spectroscopy, 2015)
Drop-coating deposition Raman (DCDR) spectroscopy is based on the measurement of a sample that has been preconcentrated by being dried on a special hydrophobic plate. In addition to its higher sensitivity, the advantage of DCDR over the conventional Raman spectroscopy is the small sample volume needed, the lack of interference from solvents, and the capability of segregating any impurities present and separating components in more complex samples. In this study, DCDR spectroscopy was employed to investigate the complex of the cationic copper(II) 5,10,15,20-tetrakis(1-methyl-4-pyridyl) porphyrin (CuTMPyP) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) liposomes. Drop-coating deposition Raman spectra were treated using factor analysis (FA), which led to the following conclusions: (i) the distribution of CuTMPyP in the complex is not homogenous, (ii) the DCDR technique segregates complexed and noncomplexed parts of the sample, (iii) the spectral changes caused by the drying process and by the interaction of CuTMPyP with the DPPC liposomes can be distinguished, and (iv) the porphyrin molecules interacting with DPPC affect both the order-disorder properties of the lipid chains and the lipid head.
Keywords: Ramanova spektroskopie; Porphyrins; Spectrum Analysis, Raman; porfyriny; Liposomes; liposomy; membrány umělé; Membranes, Artificial